Aplikasi Presensi Pt Meteor Berlian Media Nusantara (Jateng Pos) Menggunakan RFID - Bayu Sejati, Rachmad; Wismarini, TH.Dwiati (Information Technology and Telematics, 2018)
Abstract- PT Meteor Berlian Media Nusantara (Jateng Pos Daily) is a company in printing and publishing. At this PT, print a daily newspaper, Central Java Daily. The Central Java Post daily printed at least 63,000 copies every day. From advertising to business news and so on. The company has around 30 daily employees including editors, journalists and layouts. So that daily employee data must be well organized, especially in the field of daily employee attendance. The application was developed using Visual Basic 2010 which makes it easy for researchers to create applications because it is easier and lighter and SQL Server is the database. so that it can manage and distribute attendance data information at PT Meteor Berlian Media Nusantara (Jateng Pos Daily) quickly, precisely and accurately.